Quantifying the interrelationship between friction, wear, and noise: a comparative study on aluminum, brass, and steel - Tian, Yang; Khan, Muhammad; Deng, Haoxuan; Omar, Intisar (Elsevier, 2025)
Friction-induced wear and noise affect the performance and lifespan of industrial components, yet models often address them separately. This study proposes a model linking wear volume, coefficient of friction (COF), and noise. Ball-on-disc tribometer tests on 6082 aluminum, UNS C38500 brass, and 304 stainless steel were conducted under various loads and speeds. Key findings reveal thermal expansion affects wear in aluminum but minimally impacts brass and steel. The aluminum-based equation also predicts noise for brass and steel, with errors under 10 % within 5–15 N loads and 0.21–0.63 m/s speeds, suggesting broader applicability. This model provides a simplified approach to linking friction, wear, and noise, offering potential improvements in wear monitoring and noise control for mechanical systems.
Keywords: Mechanical Engineering & Transports; 4014 Manufacturing engineering; 4017 Mechanical engineering; Wear; Friction; Tribometer; Friction noise